2014
DOI: 10.3109/01443615.2014.961906
|View full text |Cite
|
Sign up to set email alerts
|

Association between pelvic organ prolapse and bone mineral density in postmenopausal women

Abstract: Both pelvic organ prolapse (POP) and osteoporosis are age-related diseases in older aged women. Both POP and bone metabolism may be associated with collagen metabolism. Our study determined the relationship between POP and bone mineral density (BMD) of the lumbar spine and femur neck in postmenopausal women. We selected 554 postmenopausal women (aged 50-79 years) and divided them into two groups (moderate to severe POP and absent to mild POP). We compared the BMDs of the lumbar spine and femur neck between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The high prevalence of POP and osteoporosis in postmenopausal women raises the possibility that the association is related to low estrogen levels and changes in the amount and quality of collagen and connective tissue [12,16]. Pelvic floor collagen is mainly composed of type I and III collagen, and type I collagen is also the principal component of the organic matrix of the bone [13]. Estrogen acts on collagen, which increases the strength of muscle and connective tissue, and on biochemical molecules that prevent the decomposition of collagen and elastin [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The high prevalence of POP and osteoporosis in postmenopausal women raises the possibility that the association is related to low estrogen levels and changes in the amount and quality of collagen and connective tissue [12,16]. Pelvic floor collagen is mainly composed of type I and III collagen, and type I collagen is also the principal component of the organic matrix of the bone [13]. Estrogen acts on collagen, which increases the strength of muscle and connective tissue, and on biochemical molecules that prevent the decomposition of collagen and elastin [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the relationship between POP and osteoporosis should be clarified among women of the same race. Among Korean women, Lee et al reported that the BMDs of the lumbar spine and femoral neck were not significantly different between the moderate-to-severe POP group and the no-to-mild POP group among 554 postmenopausal women aged 50-79 years [13]. However, the authors reported that women with severe POP had an increased risk of osteoporotic fractures, suggesting that the severity of POP can affect the relationship between POP and osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(9) Vaginal pruritus and malodorous discharge [29]. (10) Loss of pelvic muscle tone manifested as prolapse of reproductive or urinary tract organs [30]. (11) Urinary frequency, urgency, and incontinence due to decreased urine pH.…”
Section: Physical Changesmentioning
confidence: 99%